2016
DOI: 10.1038/srep32977
|View full text |Cite
|
Sign up to set email alerts
|

Gamma radiation at a human relevant low dose rate is genotoxic in mice

Abstract: Even today, 70 years after Hiroshima and accidents like in Chernobyl and Fukushima, we still have limited knowledge about the health effects of low dose rate (LDR) radiation. Despite their human relevance after occupational and accidental exposure, only few animal studies on the genotoxic effects of chronic LDR radiation have been performed. Selenium (Se) is involved in oxidative stress defence, protecting DNA and other biomolecules from reactive oxygen species (ROS). It is hypothesised that Se deficiency, as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 50 publications
2
22
1
2
Order By: Relevance
“…If not removed, the DNA polymerases may misincorporate adenine opposite 8‐oxoG, which may be removed by MutY that excises adenine from 8oxoG:A base pairs, giving a new chance for Ogg1 to remove 8‐oxoG. Studies of Ogg1‐deficient mice have shown no significant elevation of the spontaneous Pig‐a mutation frequency , which correlates well with the lack of cancer phenotype in this mouse model. The Ogg1‐deficient mice have been subjected to BaP, to Se deficiency and to low dose rate gamma irradiation without the Pig‐a ‐mutant cell frequency exceeding the wild‐type levels, suggesting that the DNA damage levels induced are being repaired via other backup DNA repair systems.…”
Section: Usefulness In Basic Sciencementioning
confidence: 62%
See 4 more Smart Citations
“…If not removed, the DNA polymerases may misincorporate adenine opposite 8‐oxoG, which may be removed by MutY that excises adenine from 8oxoG:A base pairs, giving a new chance for Ogg1 to remove 8‐oxoG. Studies of Ogg1‐deficient mice have shown no significant elevation of the spontaneous Pig‐a mutation frequency , which correlates well with the lack of cancer phenotype in this mouse model. The Ogg1‐deficient mice have been subjected to BaP, to Se deficiency and to low dose rate gamma irradiation without the Pig‐a ‐mutant cell frequency exceeding the wild‐type levels, suggesting that the DNA damage levels induced are being repaired via other backup DNA repair systems.…”
Section: Usefulness In Basic Sciencementioning
confidence: 62%
“…We recently published a study on single and combined effects of continuous chronic low dose rate gamma exposure and selenium deprivation via diet in a mouse model with deficient repair of oxidized DNA (8‐oxoguanine DNA glycosylase‐deficient mice; Ogg1 −/− ) and control animals. The main result of this study was that gamma radiation given in a more environmentally relevant exposure manner (1.48 mGy/hr for 45 days to a total dose of 1.5 Gy) is indeed genotoxic in mice . One of several methods used to determine genotoxic effects was the Pig‐a gene mutation analyses.…”
Section: Pig‐a In Micementioning
confidence: 97%
See 3 more Smart Citations